الرقمنة والإدارة الإلكترونية وأثرها في إدارة الموارد البشرية بالجماعات الإقليمية في الجزائر - دوش,حمزة (University of Eloued جامعة الوادي, 2024)
تعمل إدارة الموارد البشرية الرقمية أو الإلكترونية على القيام وبشكل أساسي لإدارة جميع الوظائف عبر التطبيقات والانترنت، وهو موضوع يفرض التحول الرقمي لجميع المؤسسات سواء ما تعلق ذلك بالقطاع الخاص أو العمومي على حدٍّ سواء، بغية تحقيق الفعالية ومواكبة التحولات العالمية الحاصلة في هذا المجال، وتظهر في ذلك مجموع الإصلاحات التي أدخلتها الدولة الجزائرية على مستوى الإدارات العمومية والإقليمية وجميع أدوارها خاصة ما تعلق منها بإدارة شؤون الموظفين على مستوى البلديات، تتطرق هذه الدراسة إلى مفهومها وكيف تطورت، ومحدداتها المختلفة، ونظرة الموظفين، ومناقشة الجوانب المختلفة لذلك. توصلت الدراسة إلى الدور المهم للإدارة الالكترونية للموارد البشرية وتحسين وظائفها المعاصرة بمختلف أبعادها، مع ضرورة استمرار عملية التقويم للسياسات الخاصة بالإصلاحات، كما أبانت أيضا عن وجود علاقة متلازمة بين الإدارة الإلكترونية ومؤشر إدارة شؤون الموظفين على مستوى البلديات، في دراسة تهدف إلى توضيح أهمية تطبيق الإدارة الإلكترونية على مستوى إدارة الموارد البشرية في البلديات بين معايير تعميم الأداء الإلكتروني لجميع الوظائف وما تتطلبه مقتضيات العصرنة. Abstract: Electronic human resources management works mainly to manage all jobs via Internet applications as it is a topic that imposes digital transformation to all institutions. Whether related to special or general security, to achieve effectiveness and then keep rapidity with global transformations in the domain. Its appear in the field of reforms introduced by the Algerian state on the level of public and regional administrations in addition to all their roles, especially those related to the management of personnel affairs at the municipal level. This study addresses its concept how it developed its various determinants, and the employees’ outlook, also discusses the various aspects of it. The survey tackled the fundamental role of electronic management of human resources and developing its contemporary duties in its different dimensions. With the necessity of continuing the investigating process for policies. It also detected the existence of a linkage between electronic management and the indicator of personnel management municipal; the study aimed to clarify the importance of applying electronic management at the level of human resources management in municipalities, between the standards for generalizing electronic performance for all jobs and what the requirements of novelty require.
Keywords: الإدارة الإلكترونية; إدارة الموارد البشرية المعاصرة; الجماعات الإقليمية; البلدية الإلكترونية; Electronic management; Neoteric human resources management; Regional groups; The electronic municipality